Health States of Exception: unsafe non‐care and the (inadvertent) production of ‘bare life’ in complex care transitions - Waring, Justin; Bishop, Simon (Sociology of health & illness, 2020)
This paper draws on the work of Giorgio Agamben to understand how the social organisation of care transitions can reduce people to their ‘bare’ life thereby making harmful and degrading treatment seemingly legitimate. The findings of a 2‐year ethnographic study show how some people experience hospital discharge as undignified, inhumane and unsafe process, expressed through their lack of involvement in care planning, delayed discharge from hospital and poorly coordinated care. Our analysis explores how these experiences stem from the way patients are constituted as ‘unknown’ and ‘ineligible’ subjects and, in turn, how professionals become ‘not responsible’ for their care. The result being that the person is reduced to their ‘bare’ life with limited value within the care system. We suggest that the social production of ‘bare life’ is an inadvertent consequence of reconciling and aligning multiple disciplines within a complex care system.